Supply Chain Management of Industrial Enterprise Based on the Participation in Network Architecture Holdings (Case Study: SPV) - Pavel Ryabchuk; Igor Baev; Olga Zubkova; Dmitriy Korneev (International Journal of Supply Chain Management, 2020)
Abstract— The modern industry of the Russian Federation is experiencing an acute shortage of long-term investment resources for technological re-equipment programs aimed at import substitution. The purpose of the study is to identify topical issues of the supply chain management at an industrial enterprise that has become an SPV in a business network. The study is mainly based on the methodology for modeling supply chain management of the recipient enterprise and the method of discounting its cash flows generated with the participation of the industrial enterprise in the leasing process. The proposed concept of systematic management of the leasing process based on business networks allows investors to focalize investment resources on the basis of a set of management methods in order to accelerate the launch of industrial production and increase capitalization. The proposed systematic supply chain management concept is of practical value for a wide range of organizations considering the possibility of using tools for technological re-equipment of industrial production in the context of platform-based business networks. Implementation of the supply chain in SPV is showed at creation of a continuous innovations flow, reduction of technological development costs and unfirming system for development.